Limited Role of Hair Cortisol and Cortisone Measurement for Detecting Cortisol Autonomy in Patients With Adrenal Incidentalomas - Puglisi, Soraya; Leporati, Marta; Amante, Eleonora; Parisi, Alice; Pia, Anna Rosa; Berchialla, Paola; Terzolo, Massimo; Vincenti, Marco; Reimondo, Giuseppe (Frontiers in Endocrinology, 2022)
Several studies demonstrated the diagnostic accuracy of hair glucocorticoid measurement in patients with overt Cushing syndrome, but few data are available for patients with adrenal incidentaloma (AI) and cortisol autonomy. The aim of our study was to assess whether measurement of 5 corticosteroid hormones with the ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method in the keratin matrix is useful to stratify patients with AI by the presence of autonomous cortisol secretion [ACS] (defined as serum cortisol after 1 mg dexamethasone suppression test (DST) > 138 nmol/L) or possible ACS [PACS] (defined as serum cortisol after 1 mg DST > 50 nmol/L but <138 nmol/L). We analysed data of 67 AI patients (32 with cortisol autonomy) and 81 healthy subjects. We did not find any significant statistical difference comparing hair cortisol, cortisone and 20β-dihydrocortisol concentrations between healthy controls and AI patients, while 6β-hydroxycortisol and 11-deoxycortisol were undetectable. Moreover, no significant difference was found in hair cortisol, cortisone and 20β-dihydrocortisol levels of AI patients with or without cortisol autonomy. Finally, we did not find any correlation in patients with AI between hormonal concentrations in the keratin matrix and serum, salivary and urinary cortisol levels, or with body mass index. In conclusion, our findings suggest that hair glucocorticoids measurement is not suitable as a diagnostic test for cortisol autonomy (ACS and PACS).